1994
DOI: 10.1177/089198879400700404
|View full text |Cite
|
Sign up to set email alerts
|

The Zung Self-Rating Depression Scale: Screening for Depression Among the Hong Kong Chinese Elderly

Abstract: Two studies were conducted respectively to examine the reliability and validity of the standard Zung Self-rating Depression Scale (SDS), and a 10-item shorter version of the same test. In particular, the scale's usefulness as a screening instrument for depression among the Hong Kong Chinese elderly was investigated. In addition to the SDS, the Geriatric Depression Scale and the Chinese Hamilton Depression Scale were used to assess the convergent validity of the SDS. Data were collected from 113 nondepressed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(69 citation statements)
references
References 13 publications
1
68
0
Order By: Relevance
“…Internal consistency reliability in past research was a .92 coefficient alpha (Zung, 1986). In a Chinese and a Taiwanese population, reliability, Cronbach's alpha of the SDS, was consistently greater than .80 (Lee et al, 1994;Leung, Lue, Lee, & Tang, 1998). Lee et al (1994) reported convergent validity with the Geriatric Depression Scale (GDS; r = .88) and the Chinese Hamilton Depression Scale (CHDS; r = .86).…”
Section: Pulmonary Functional Status Scale (Pfss)mentioning
confidence: 89%
“…Internal consistency reliability in past research was a .92 coefficient alpha (Zung, 1986). In a Chinese and a Taiwanese population, reliability, Cronbach's alpha of the SDS, was consistently greater than .80 (Lee et al, 1994;Leung, Lue, Lee, & Tang, 1998). Lee et al (1994) reported convergent validity with the Geriatric Depression Scale (GDS; r = .88) and the Chinese Hamilton Depression Scale (CHDS; r = .86).…”
Section: Pulmonary Functional Status Scale (Pfss)mentioning
confidence: 89%
“…Many researchers have translated it into Chinese (see Appendix E) and validated it among Chinese samples (e.g. Lee et al, 1994;Liu, Ma, Kurita, & Tang, 1998). Previous studies also indicated that students with higher levels of acculturative stress would have lower levels of life satisfaction (Pan et al, 2008;Pan et al, 2010).…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of this study, participants were selected if they met the following inclusion criteria at the initial consultation: (1) 60 years or older; (2) absence of cognitive impairment, as defined by a score of less than 24/30 on the Mini-Mental State Examination (MMSE) (Folstein et al, 1975); (3) absence of depression, as defined by a score of 70 or more on Tucker's short interviewer-assisted depression scale (short Zung) (Tucker et al, 1987), which has been validated for the elderly (Tucker et al, 1987;Lee et al, 1994;Sinoff et al, 2002).…”
Section: Participantsmentioning
confidence: 99%